Depression in a household population sample in Aracaju (Sergipe, Brazil) - Menezes, Mariana Siqueira; Faro, André (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2019)
This study aimed to detect the prevalence of symptoms of depression in a representative household population sample from Aracaju (Sergipe, Brazil), as well as estimating the chances of positive diagnostic screening of depression, based on socio-demographic and general health profiles. The sample was composed of 690 participants. The Beck Depression Inventory (BDI) and questionnaires about socio-demographic and health-related data were used. Almost 35% of participants had positive screening diagnosis of depression. The Logistic Regression showed that those people who perceived themselves as sick, non-religious, lacked a college degree, smokers or who were obese, smokers composed the profile of individuals with a greater chance to be in the BDI positive group. These findings are important due to the lack of similar studies in Brazilian Northeast region.